Long-Term Outcomes of Pediatric Intracardiac Masses: Clinical Course and Tumor Behavior in a Single-Center Experience - Arıcı, Şule; Çırakoğlu, Ahmed Mahmud; Akalın, Figen (The European Research Journal, 2026)
Objective: We aimed to evaluate the clinical characteristics, diagnostic pathways, echocardiographic and Holter findings, treatment strategies, and long-term outcomes of children with intracardiac masses, and to explore factors associated with tumor regression. Methods: This retrospective observational study included children with echocardiographically confirmed intracardiac masses followed at a tertiary pediatric cardiology center between January 2010 and January 2022. Demographic and clinical characteristics, tumor features, serial echocardiographic measurements, 24-hour Holter recordings, treatment strategies, and follow-up outcomes were analyzed. Results: A total of 20 patients were included. Rhabdomyoma was the most common tumor type (60%, n=12), followed by fibroma (30%, n=6). Most patients were asymptomatic or mildly symptomatic at presentation (90%, n=18). Clinically significant arrhythmias were observed in 15% (n=3), predominantly in patients with fibromas. Tumor size reduction was observed in 40% (n=8) of patients. All patients diagnosed during the fetal period (15%, n=3) exhibited tumor size reduction; all had rhabdomyomas. Everolimus was administered in 25% (n=5) of patients, with tumor size reduction observed in 80% (n=4) of treated cases; however, this was not statistically significant (P=0.253). Left ventricular systolic function remained preserved in all patients during follow-up. Conclusion: Pediatric intracardiac masses are predominantly benign but show heterogeneous clinical behavior. Tumor regression was more frequent in rhabdomyomas; however, this may reflect tumor type distribution. Arrhythmias were more frequent in fibromas, supporting rhythm surveillance. Everolimus may be considered in selected patients; however, findings should be interpreted with caution due to limited sample size and potential selection bias, and require confirmation in larger studies.